PENGARUH MEDIA FOLDING PAPER CRAFTS TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI 141 PALEMBANG - Agustin, Vella; Dian Lestari, Neta; Lara Syaflin, Sylvia (Universitas PGRI Palembang, 2025)
This study examines the influence of folding paper crafts media on the learning outcomes of grade V mathematics of Elementary School 141 Palembang building space material because the results of learning grade V Mathematics on space building material are still low as evidenced by the value of half of the population in grade V is still below KKM. The purpose of this study was to determine the effect of folding paper crafts media on grade V mathematics learning outcomes at SD141 Palembang.The approach used is quantitative experimentation. The research design used true experimental design Posttest- Only control design. The results of the observation sheet of student activeness from the research found that the activeness of students in learning mathematics using folding paper crafts media had a value of 92% in the very active category. The results of the study showed that the data obtained by the Posttest score of the Experimental class showed an average result of 74.81 while in the control class the average result was only 56.29. Based on the normality test, it is stated that the sample comes from a normal population. Based on the homogeneity test, it is stated that the sample comes from a homogeneous population, then based on the hypothesis test, the sig value is known. (2-tailed) with t-test is 0.000. Because the probability value is less than 0.05, and the calculated t value is 4.497 > ttable is 1.674. Thus Ho (null hypothesis) is rejected and Ha (alternative hypothesis) is accepted. Based on the results of the analysis and discussion of test data, it can be concluded that there is an influence after being treated using folding paper crafts media on the learning outcomes of grade V Mathematics at Elementary School 141 Palembang.